2023
DOI: 10.1364/ol.482351
|View full text |Cite
|
Sign up to set email alerts
|

Super tiny quartz-tuning-fork-based light-induced thermoelastic spectroscopy sensing

Abstract: In this Letter, a sensitive light-induced thermoelastic spectroscopy (LITES)-based trace gas sensor by exploiting a super tiny quartz tuning fork (QTF) was demonstrated. The prong length and width of this QTF are 3500 µm and 90 µm, respectively, which determines a resonant frequency of 6.5 kHz. The low resonant frequency is beneficial to increase the energy accumulation time in a LITES sensor. The geometric dimension of QTF on the micrometer scale is advantageous to obtain a great thermal expansion and thus ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…3 In view of the advantages of 1.6-μm band laser, it has important applications in the fields of laser radar, industry, military, gas sensing, and optical communication. [4][5][6][7] For example, in the military, a 1.6-μm laser has excellent stable performance under different atmospheric conditions. Thus, the U.S. Navy believes that a 1.6-μm laser is suitable for use in coastal environments and can be used as an advanced laser weapon to provide high-precision strike means to intercept antiship missiles, drones, and other targets in conjunction with proximity weapons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In view of the advantages of 1.6-μm band laser, it has important applications in the fields of laser radar, industry, military, gas sensing, and optical communication. [4][5][6][7] For example, in the military, a 1.6-μm laser has excellent stable performance under different atmospheric conditions. Thus, the U.S. Navy believes that a 1.6-μm laser is suitable for use in coastal environments and can be used as an advanced laser weapon to provide high-precision strike means to intercept antiship missiles, drones, and other targets in conjunction with proximity weapons.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the advantages of 1.6‐μm band laser, it has important applications in the fields of laser radar, industry, military, gas sensing, and optical communication 4–7 . For example, in the military, a 1.6‐μm laser has excellent stable performance under different atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…PAS is studied by research recent years and many types of cells were reported. For getting higher sonic signal, traditional photoacoustic cells (PAC) were designed by metal parts with bigger volume as well as resonator of 6–10 mm 13–16 . With the developing of 3D print, compact and integrally‐formed cells can be manufactured.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of the vertical concentration profiles of atmospheric trace gases is very important for understanding the physics, chemistry, dynamics, and radiation budget of the atmosphere as well as validating chemical models and satellite observations [ 1 , 2 , 3 , 4 ]. Laser heterodyne radiometer (LHR), as a kind of passive remote sensing technology, was introduced and developed in the 1970s to meet the needs of observing the ozone hole in the atmosphere [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%